Lappiske eventyr og sagn. - Qvigstad, J. (Just), 1853-1957. (Oslo : H. Aschehoug & Co.; Cambridge, Mass. : Harvard University Press; [etc., etc.], 1927)
Authorities given in "Forord" of each volume. Lappish text with Norwegian translation on opposite pages. Mode of access: Internet.